2007
DOI: 10.1007/bf03004175
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms, socio-economic background, sense of control, and cultural factors in University students from 23 Countries

Abstract: We measured depressive symptoms with the Beck Depression Inventory in 17,348 university students from 23 high-, middle-, and low-income countries, and assessed associations with individual level and ecological level factors using multi-level random effects regression modelling. Wide variations in depressive symptoms were observed between countries, with lower levels in Western and Southern Europe and South and North America, intermediate levels in Central and Eastern Europe, and higher levels in Pacific-Asian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
234
13
16

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(286 citation statements)
references
References 48 publications
23
234
13
16
Order By: Relevance
“…Eight articles reported results from multi-country studies 12,27,29,[31][32][33][34][35] ; ten studies were conducted in the USA 28,30,[36][37][38][39][40][41][42][43] ; three studies were carried out in the UK [44][45][46] ; two articles reported results from a study carried out in Brazil 47,48 ; one study was conducted in Australia 49 , one in Mexico 50 , one in Spain 51 , and one in South Africa 26 (Table 1).…”
Section: Figure 1 About Herementioning
confidence: 99%
See 3 more Smart Citations
“…Eight articles reported results from multi-country studies 12,27,29,[31][32][33][34][35] ; ten studies were conducted in the USA 28,30,[36][37][38][39][40][41][42][43] ; three studies were carried out in the UK [44][45][46] ; two articles reported results from a study carried out in Brazil 47,48 ; one study was conducted in Australia 49 , one in Mexico 50 , one in Spain 51 , and one in South Africa 26 (Table 1).…”
Section: Figure 1 About Herementioning
confidence: 99%
“…One article included university students 35 , one included 11, 13 and 15-year-old students 31 and one sampled women with infant children 40 . Twenty-two articles assessed psychiatric diagnoses 12,[26][27][28][29][30]32,[34][35][36][37][39][40][41][42][43][44][45][46][47] , whereas three assessed psychological distress/symptoms or mental well-being/functioning 31,33,49 . One article assessed both psychiatric diagnosis and psychological symptoms 38 , and one article reported use of mental health services 48 .…”
Section: Table 1 About Herementioning
confidence: 99%
See 2 more Smart Citations
“…Previous study of Steptoe et al also showed that Asian countries had the highest incidence of depression as compared to other countries [18]. However, this percentage is quite high as compared to the findings of Sreeramareddy et al (20%) and Chan DW (21%) [19,20].…”
Section: Discussionmentioning
confidence: 70%